ANALISIS PEMBELAJARAN SEJARAHDI PONDOK PESANTREN AL-MUAYYAD SURAKARTA - Ishaqro, Alfi Hafidh; Joebagio, Hermanu; Sariyatun, S. (Sebelas Maret University (UNS), 2016)
The paradigm of learning at the school who just explore the science of Islam have now been displaced. It is characterized by the establishment of formal schools within the scope of the boarding school, so changing the paradigm of a typical boarding school to become an institution. The purpose of this study is to describe the planning, implementation, evaluation, and constraints in the learning process in the history of class X SMA Al-Muayyad Surakarta.Methods: Penelitianini a qualitative descriptive research with case study research strategy. Data collection techniques used were interviews, observation, and document analysis. The sampling technique purposive sampling. Data were analyzed using interactive model by HB Sutopo.Results: 1) The teacher makes the planning and teaching of history with a good device and adjust the conditions, situations and needs of students; 2) in the implementation of the teaching of history, teachers tend to be less creative and overly dominate the learning process by simply using the lecture method; 3) in the teacher evaluation process using two evaluation techniques, namely formative assessment and summative assessment; 4) problems were found during the learning process includes three aspects, namely from the aspect of students, teachers aspects, and metode.5) recommended the integration between learning history by considering the diversity and multicultural learning ethnic background of students who are spread throughout the archipelago.Implications: Learning history in high school Al-Muayyad role in shaping national identity, intellectual identity and Islamic identity of the student or students. So that graduates produced boarding Al-Muayyad can continue to maintain the identity of the school and transform Ahlusunnah wal Jamaat Islamic characteristics to all levels of society to keep the Homeland of the threat of national disintegration.